The Flint Hills: A Major Chapter in Potawatomi Migration - Jon Boursaw (Symphony in the Flint Hills, 2011)
As a member of the Citizen Potawatomi Nation, I am proud to be a direct descendant of two greatgreat-grandfathers who were considered Headmen or Tribal Leaders of the Potawatomi in Kansas. In the mid-1800’s, a large portion of the northern area of the Flint Hills was within the boundaries of the Potawatomi Indian Reservation.
Keywords: Chief Wabunsee; Native Americans; Potawatomi Nation; Potawatomi; Tribal; Indian; Reservation; Trail of Death; Bourassa; Ogee